The Effect of Headmaster Leadership and Achievement Motivation on Competency of State High School Teachers in Manado City - Sophia Pongoh; Sjeddy Watung (AIBPM Publisher, 2018)
The purpose of this study is to analyze the influence of principals' leadership and achievement motivation on the competence of teaching high school teachers in the city of Manado.The research method is a survey method with regression analysis by first conducting a prerequisite test, namely data normality test and data linearity. The next is to analyze the data with simple regression and multiple regression then the significance test is performed.The results of data analysis show that: (1) principals' leadership positively influences the competence of teaching high school teachers in the city of Manado; (2) achievement motivation positively influences the competence of teaching high school teachers in the city of Manado; (3) jointly the principal's leadership and achievement motivation had a positive effect on the competence of teaching teachers in senior high schools in the city of Manado. Keywords: teaching competency, principal leadership, achievement motivation.